2019
DOI: 10.1371/journal.pone.0226394
|View full text |Cite
|
Sign up to set email alerts
|

Tapped out or barely tapped? Recommendations for how to harness the vast and largely unused potential of the Mechanical Turk participant pool

Abstract: Mechanical Turk (MTurk) is a common source of research participants within the academic community. Despite MTurk’s utility and benefits over traditional subject pools some researchers have questioned whether it is sustainable. Specifically, some have asked whether MTurk workers are too familiar with manipulations and measures common in the social sciences, the result of many researchers relying on the same small participant pool. Here, we show that concerns about non-naivete on MTurk are due less to the MTurk … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(78 citation statements)
references
References 34 publications
(51 reference statements)
0
70
0
Order By: Relevance
“…There are some aspects researchers should consider when starting out with running online studies or transferring lab-based experiments to online systems [59,75,76] (see Figure 2). To a certain extent, creating successful online experiments is similar to app development: one needs to think of a coherent framework and constantly worry about what the users are doing with the 'product' and whether they are using it as intended-without many opportunities for direct feedback.…”
Section: Considerations For Successful Online Studiesmentioning
confidence: 99%
“…There are some aspects researchers should consider when starting out with running online studies or transferring lab-based experiments to online systems [59,75,76] (see Figure 2). To a certain extent, creating successful online experiments is similar to app development: one needs to think of a coherent framework and constantly worry about what the users are doing with the 'product' and whether they are using it as intended-without many opportunities for direct feedback.…”
Section: Considerations For Successful Online Studiesmentioning
confidence: 99%
“…The fraction of participants giving at least one unexpected CRT response is 15% among baseline workers, 29% among pre-quarantine workers, 38% among post-quarantine workers, 19% among Prolific workers, and 34% among Lucid workers. Furthermore, the fraction of MTurk workers with at least one unexpected response in a 2019 study with no restrictions other than being located in the US was of 25% (5). Thus, new MTurk workers do not seem appreciably worse than participants from Lucid but they do seem to perform worse on the CRT than Prolific users and their MTurk counterparts a year ago.…”
Section: Discussionmentioning
confidence: 92%
“…Here we consider the impact of the current pandemic on subject pool composition by looking at 15,608 responses given to studies conducted by our group on MTurk between February and July 2020. Moreover, by exploiting a recent change in our recruitment approach, we are better suited to attract new participants, to track unrestricted and traditionally restricted samples over time (5) and, relative to usual recruitment restrictions, to anticipate eventual surgesas many of the new accounts considered would meet their criteria within a few weeks (6).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the sample size of this study is limited based on Krejcie and Morgan (1970), who recommended a sample size of 382 for a population size of more than 75,000. A most recent study (Robinson et al, 2019) indicated the Amazon Mechanical Turk panel, where our survey was distributed, have at least 250,810 workers worldwide and 226,500 workers in the United States. There were 80,000-85,000 active workers per year from 2016 to 2018 (Robinson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A most recent study (Robinson et al, 2019) indicated the Amazon Mechanical Turk panel, where our survey was distributed, have at least 250,810 workers worldwide and 226,500 workers in the United States. There were 80,000-85,000 active workers per year from 2016 to 2018 (Robinson et al, 2019). Accordingly, the researchers can surmise that the generalizability of the results is constrained by the sample frame limitation.…”
Section: Discussionmentioning
confidence: 99%